Alarming decline and range reduction of the highly threatened Great Bustard Otis tarda in Morocco. (1st September 2016) - Alonso, Juan Carlos; Palacín, Carlos; Onrubia, Alejandro; Aboulouafae, Rachid; Amezian, Mohamed; El Idrissi Essougrati, Abdelaziz; El Khamlichi, Rachid; Noaman, Mohamed
Abstract : A Great Bustard Otis tarda survey carried out in spring 2015 in Morocco confirmed the decline of this highly endangered population. Bustards were only seen at two of the seven leks occupied ten years ago. The total number of birds counted was 40-44, which represents a 40% decline over the last decade. The sex-ratio was still strongly female-biased (1 male: 3 females), but less than in previous surveys, which suggests that trophy hunting has not been the major mortality cause in recent times. The productivity was 0.29-0.33 juveniles per female, the highest ever recorded in this population, suggesting that breeding success doesn't represent the main problem for the survival of this population. Based on the recent development of the power line network at some areas, the main threat today is probably collision with power lines. Reducing this mortality cause should be considered a high conservation priority.